2018
DOI: 10.1371/journal.pone.0191357
|View full text |Cite
|
Sign up to set email alerts
|

Risk preferences impose a hidden distortion on measures of choice impulsivity

Abstract: Measuring temporal discounting through the use of intertemporal choice tasks is now the gold standard method for quantifying human choice impulsivity (impatience) in neuroscience, psychology, behavioral economics, public health and computational psychiatry. A recent area of growing interest is individual differences in discounting levels, as these may predispose to (or protect from) mental health disorders, addictive behaviors, and other diseases. At the same time, more and more studies have been dedicated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 84 publications
(67 reference statements)
1
48
0
Order By: Relevance
“…Interestingly, and providing further support for the unified system perspective, a conjunction analysis again revealed that the same striatal voxels represented undiscounted and discounted utility (with each side of the conjunction statistically controlling for the other; figure 2), further suggesting that this region might support the integration of undiscounted utility and delay to drive temporal discounting. Also of note, as shown behaviourally in Lopez-Guzman et al [89], the temporal discounting model that best fit the neural data was the modified hyperbolic model, providing converging evidence that the brain implements this particular algorithm [89,96].…”
Section: (Online Version In Colour)mentioning
confidence: 63%
See 3 more Smart Citations
“…Interestingly, and providing further support for the unified system perspective, a conjunction analysis again revealed that the same striatal voxels represented undiscounted and discounted utility (with each side of the conjunction statistically controlling for the other; figure 2), further suggesting that this region might support the integration of undiscounted utility and delay to drive temporal discounting. Also of note, as shown behaviourally in Lopez-Guzman et al [89], the temporal discounting model that best fit the neural data was the modified hyperbolic model, providing converging evidence that the brain implements this particular algorithm [89,96].…”
Section: (Online Version In Colour)mentioning
confidence: 63%
“…(a) Bias in estimated discount rate from simulated intertemporal choice data at different levels of risk preference (from risk averse to risk seeking). Bias is computed as the difference between standard hyperbolic model (Mazur [59]) and the extended hyperbolic model (Lopez-Guzman et al [89]), which discounts utility rather than value. At risk aversion levels (a , 1), the standard model overestimates the discount rate and at risk seeking levels (a .…”
Section: The Neural Implementation Of Temporal Discounting and Risk Pmentioning
confidence: 99%
See 2 more Smart Citations
“…Our method assumes that individuals' utility functions are approximately linear over the range of stakes involved (this is common in the experimental literature on DD). However, a more concave utility function can be confounded with a higher discount rate (Andersen et al, 2008;Frederick et al, 2002;Lopez-Guzman et al, 2018). In this vein, our results could also be partially explained if Gitanos have a more concave utility function compared to the majority.…”
Section: Discussionmentioning
confidence: 81%